2005
DOI: 10.1002/aoc.579
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of arsenosugars in marine sediment

Abstract: In the marine environment, arsenic accumulates in seaweed and occurs mostly in the form of arsenoribofuranosides (often called arsenosugars). This study investigated the degradation pathways of arsenosugars from decaying seaweed in a mesocosm experiment. Brown seaweed (Laminaria digitata) was placed on top of a marine sediment soaked with seawater. Seawater and porewater samples from different depths were collected and analysed for arsenic species in order to identify the degradation products using high-perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…3 and Table S5). This rapid loss of arsenolipids was similar to that found for water-soluble arsenicals in decomposing algae as reported in our previous study (Duncan et al 2014a) and by others (Edmonds et al 1982;Pengprecha et al 2005;Navratilova et al 2011;Ojo and Onasanya 2013). By the latter stages of the experiment (days 45-60), almost all the AsPLs had degraded and only AsHC388 was detected in measurable concentrations (Fig.…”
Section: Release and Degradation Of Arsenolipid Speciessupporting
confidence: 89%
“…3 and Table S5). This rapid loss of arsenolipids was similar to that found for water-soluble arsenicals in decomposing algae as reported in our previous study (Duncan et al 2014a) and by others (Edmonds et al 1982;Pengprecha et al 2005;Navratilova et al 2011;Ojo and Onasanya 2013). By the latter stages of the experiment (days 45-60), almost all the AsPLs had degraded and only AsHC388 was detected in measurable concentrations (Fig.…”
Section: Release and Degradation Of Arsenolipid Speciessupporting
confidence: 89%
“…DMAE has been detected in macro-algae in some studies; 97 however, often it is not present. 6−10,18−21,23−27,30,34,35,76,78,80,81,84−87,89,91,94−96 DMAE has, however, been widely detected in decomposing marine macro-algae [24][25][26][27]76,78,79 and has subsequently been designated a major arsenoriboside degradation product. As will be discussed further in the next section, one of the key limitations with existing research on the arsenic species produced by marine unicellular algae is that live and dead cells are difficult to separate.…”
Section: ■ Comparisons Between Arsenic Species Distributions In Marin...mentioning
confidence: 99%
“…Dimethylarsenoribosides, commonly known as arsenoribosides or arsenosugars, are the major arsenic species found in marine macro-algae. The common arsenoribosides are differentiated by end groups containing glycerol (Gly-); phosphate (PO 4 -), sulfonate (SO 3 -), and sulfate (OSO 3 -) (Figure ). Other arsenic species such as thio-arsenoribosides, thio-dimethylarsenoethanol (thio-DMAE), dimethylarsenoethanol (DMAE), dimethylarsenoacetate (DMAA), methylarsenate (MA), dimethylarsenate (DMA) (Figure ) and As­(V) have been associated with decomposing macro-algal tissue. Arsenobetaine (AB) is the major arsenic species in almost all marine animals, typically accounting for more than 80% of the water-soluble arsenic content. ,,− Other arsenic species such as thio-arsenoribosides, thio-DMAE, DMAE, DMAA, tetramethylarsonium ion (TETRA), arsenocholine (AC), dimethylarsenopropionate (DMAP), and trimethylarsenopropionate (TMAP) (Figure ) are consistently found in marine animals, however, generally in low concentrations and proportions. ,,, …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many are dedicated to examining new compounds and their behavior, transformations and metabolic pathways because algae are crucial organisms in arsenic biogeochemistry and furthermore many algae are selected for human consumption. [1][2][3][4][5] Studies and reviews have reported on the inuence of the storage, drying and powdering conditions on total arsenic and arsenic speciation in general or for particular compounds. [6][7][8][9] On the basis of these studies, it can be deduced that no common treatment is reliable and that handling and storage protocols should be established in function of the matrix composition, environmental conditions where the sample is collected (e.g.…”
Section: Introductionmentioning
confidence: 99%